2019
DOI: 10.33263/briac95.416423
|View full text |Cite
|
Sign up to set email alerts
|

Nanodoses of melatonin induces apoptosis on human breast cancer cells co-cultured with colostrum cells

Abstract: The aim of this study was to investigate the effect of melatonin nanodoses adsorbed to PEG microspheres during different phases of the day on oxidative stress and apoptosis in human colostrum mononuclear (MN) cells co-cultured with breast cancer tumor cells (MCF-7). The MCF-7 cells were obtained from the American Type Culture Collection, and the MN cells were obtained from volunteer donors. The cells were preincubated for 24 h with or without 100 ng.mL-1 melatonin (MLT), PEG microspheres (PEG) or 100 ng.mL-1 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Studies have shown a relationship between the concentration of endogenous melatonin and the risk of breast cancer in humans. Specifically, research has suggested that melatonin [17,28] and its receptors have oncostatic properties in breast cancer models [29,30]. In this study, the melatonin levels showed concentrations similar to other works in the literature [12,31].…”
Section: Discussionsupporting
confidence: 87%
“…Studies have shown a relationship between the concentration of endogenous melatonin and the risk of breast cancer in humans. Specifically, research has suggested that melatonin [17,28] and its receptors have oncostatic properties in breast cancer models [29,30]. In this study, the melatonin levels showed concentrations similar to other works in the literature [12,31].…”
Section: Discussionsupporting
confidence: 87%
“…Breast cancer is the most common type of carcinoma in females, being the most prominent cause of cancer-related mortality in women worldwide [94,106,116,117]. The first treatment option for breast cancer is the combination between chemotherapeutic agents, radiation therapy, and surgical intervention.…”
Section: Malignant Diseasesmentioning
confidence: 99%
“…To avoid using small systemic dose or large local dose of plain chemotherapeutics, nanocarrier systems with controlled drug release can be employed. Particularly, bonetargeted drug delivery systems aim to concentrate drugs in tumor sites, protect drugs from rapid clearance, prolong their circulation times, enhance therapeutic efficacy, and reduce the systemic adverse effects [9,15,88,89].…”
Section: Drug Deliverymentioning
confidence: 99%